Business competitiveness model based on the value chain for the coking sector in Colombia - Barrera-Rodríguez, Leidy Ximena; Moya-Espinosa, Pedro Ignacio; Cortés-Rodríguez, Nubia Consuelo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The aim of this paper is to propose a model of business competitiveness based on the value chain for the coking sector in Colombia that allows its promotion and strengthening. A systematic review of the literature in the Web of Science and Scopus databases, in the period 2012-2022, was carried out to establish the documentary corpus. The categories of analysis identified converge in the competitiveness based on the value chain from which a model is proposed to integrate: the participation of social actors (government, community, academy, businessmen and unions), primary activities, support and articulate to maintain and improve competitiveness business with direct involvement in the coking sector. As a conclusion, this model contributes to the definition and direction of strategies in the transformation of coke, generating conditions of competitiveness based on customer satisfaction and the strengthening of the sector.